2017
DOI: 10.1016/j.msea.2017.01.073
|View full text |Cite
|
Sign up to set email alerts
|

The influence of microstructure on the cyclic deformation and damage of copper and an oxide dispersion strengthened steel studied via in-situ micro-beam bending

Abstract: Service materials are often designed for strength, ductility, or toughness, but neglect the effects of cyclic time-variable loads ultimately leading to macroscopic mechanical failure. Fatigue originates as local plasticity that can first only be observed on the micro scale at defects serving as stress concentrators such as inclusions or grain boundaries. Thus, a recently developed technique to perform in-situ observation of micro scale bending fatigue experiments was applied. Micro-beams fabricated from copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 61 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…This behavior can be attributed to the presence of phosphorus atoms inside the sample, which pin the grain boundaries and effectively prevent softening via grain coarsening at these stress levels. At higher stress amplitudes (> 250 MPa), the samples transition to cyclic softening, which likely results from cyclic deformation induced grain coarsening, as often observed in fatigued ultrafine grained copper specimens [33,34]. Above 300 MPa, cyclic softening weakens the sample to such an extent that it suddenly collapses during testing, which translates into a spike in plastic strain ratio, see Figure 5a.…”
Section: Ultrafine Grained Samplesmentioning
confidence: 74%
“…This behavior can be attributed to the presence of phosphorus atoms inside the sample, which pin the grain boundaries and effectively prevent softening via grain coarsening at these stress levels. At higher stress amplitudes (> 250 MPa), the samples transition to cyclic softening, which likely results from cyclic deformation induced grain coarsening, as often observed in fatigued ultrafine grained copper specimens [33,34]. Above 300 MPa, cyclic softening weakens the sample to such an extent that it suddenly collapses during testing, which translates into a spike in plastic strain ratio, see Figure 5a.…”
Section: Ultrafine Grained Samplesmentioning
confidence: 74%
“…A question to be addressed is: what happens during cyclic deformation when down-sizing the specimen to a couple of hundred nanometers? Recently, several studies have reported on the cyclic compression of crystalline nanopillars but not so many on metallic glassy pillars inside TEM [57][58][59] .…”
Section: Cyclic Deformation Of Metallic Glassesmentioning
confidence: 99%
“…Allison et al [ 48 ] performed in situ SEM microcantilever beam experiments on bioinspired nanocomposites and the deformation mechanism was similar to nacre. Howard et al [ 49 ] even studied the cyclic deformation of metal microbeam under in situ SEM bending test and found that dislocation pileup within these microbeams occurs exactly as it would in a macroscopic fatigue specimen. The in situ single point bending test can also be used in the bending of nanoscale materials; for example, Vlassov et al [ 50 ] measured Young's modulus and yield point of the Ag nanowires and even observed their plastically deformation before fracture.…”
Section: In Situ Sem Mechanical Tests Of Micro/nanomaterialsmentioning
confidence: 99%